Theorizing Oppression - Kruks, Sonia (Sapere Aude, 2013)
“Theorizing oppression” draws on a variety of Beauvoir’s works to explore the different dynamics through which oppression operates. Oppression functions so as to close down the ambiguities of embodied subjectivity and to deny freedom, most often by objectifying and treating persons as if they were things. It may, however, operate in different ways, and three primary modes of oppression are distinguished and discussed: asymmetrical recognition, indifference, and aversion. These are paradigmatically described by Beauvoir as they operate, respectively, in the spheres of gender (in The Second Sex), race (in America Day by Day), and age (in The Coming of Age). The question of how far oppressed groups may become complicit in their own oppression is also addressed: sometimes the line between oppressors and oppressed is far from unambiguous. O texto "Teorizando a opressão" baseia-se em uma variedade de obras de Beauvoir para explorar as diferentes dinâmicas através das quais a opressão opera. A opressão funciona de modo a recusar as ambiguidades da subjetividade incorporada e negar a liberdade, na maioria das vezes por definir e tratar as pessoas como se fossem coisas. Pode, no entanto, operar de maneiras diferentes, e três modos principais de opressão são diferenciados e discutidos: o reconhecimento assimétrico, a indiferença e a aversão. A forma como operam é paradigmaticamente descrita por Beauvoir, respectivamnte, nas esferas do gênero (em O Segundo Sexo), da raça (em América dia-a-dia) e da idade (em A Velhice). A questão do quanto grupos oprimidos podem tornar-se cúmplices de sua própria opressão é também abordada: às vezes a linha entre opressores e oprimidos está longe de ser inequívoca.